Characterization of nanocrystalline anatase titania: an in situ HTXRD study - Jagtap, Neelam; Bhagwat, Mahesh; Awati, Preeti; Ramaswamy, Veda (Thermochimica Acta, 2005)
Nanocrystalline titania was synthesized by the hydrolysis of titanium iso-propoxide using ultrasonication. The powder XRD patterns of the sample were recorded in static air and vacuum using a Philips X-pert Pro diffractometer equipped with a high-temperature attachment (HTK16) from room temperature (298 K) to 1173 K and were analyzed by the Rietveld refinement technique. The anatase to rutile phase transformation was observed at 1173 K for the data collected in static air. Only 3% of anatase titania transformed to rutile when the experiments were carried out at H 73 K in vacuum. The phase transformation from anatase to rutile is accompanied by a continuous increase in the crystallite size of the anatase phase from 9 nm at room temperature to 28 nm at 873 K and then to 50 nm at 1173 K in air while the process of crystallite growth was suppressed in vacuum. A linear increase in the unit cell parameters `a' and `c', and thus, an overall linear increase in the unit cell volume was observed as a function of temperature in static air as well as vacuum. The lattice and volume thermal expansion coefficients (TEC), alpha(a), alpha(c), and alpha(v) at 873 K are 8.57 x 10(-6), 8.71 x 10(-6) and 25.91 x 10(-6) K-1 in air and 18.01 x 10(-6), 14.95 x 10(-6) and 51.13 x 10(-6) K-1 in vacuum, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Anatase; HTXRD; Rietveld refinement; rutile; thermal expansion coefficient; titania

Epoxidation of indene and cyclooctene on nanocrystalline anatase titania catalyst - Ramaswamy, Veda; Awati, Preeti; Ramaswamy, A. V. (Topics in Catalysis, 2006)
Nanocrystalline anatase titania samples of different crystallite sizes were prepared by sol gel method using ultrasonication and calcination at different temperatures. The calcined samples were treated with H2O2 in order to study the role of surface hydroxyl groups present on titania in generating reactive oxygen species responsible for the epoxidation reaction. The crystallite size of the calcined samples increased from 4 to 18 nm as the calcination temperature increased from 473 to 773 K, respectively. More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline TiO2 by using ultrasonication. EPR spectral data on the H2O2-treated samples confirmed the presence of superoxide radical species. The two distinct UV bands observed at 400 and 450 nm are assigned to charge transfer of peroxide (O-2 2-) to Ti. FT-IR spectral data show that the surface hydroxyl groups are the active sites in the generation of reactive oxygen species. The catalytic activity was evaluated in a series of epoxidation reactions using indene and cyclooctene as substrates and aqueous H2O2 as oxidant. The activity was found to decrease with increase in the calcination temperature of the samples, obviously due to an increase in crystallite size and a decrease in surface hydroxyl groups. The nanoparticle titania samples show better conversion and selectivity than the standard titania (Degussa P-25). The kinetic studies revealed that the reaction followed a pseudo first order kinetics in excess of H2O2.
Keywords: cyclooctene epoxidation; epoxidation of indene; nanocrystalline anatase titania; superoxide radical on titania

Photocatalytic decomposition of methylene nanocrystalline titania prepared by different blue on methods - Ramaswamy, Veda; Jagtap, Neelam; Vijayanand, S.; Bhange, Deu S.; Awati, Preeti (Materials Research Bulletin, 2008)
Nanocrystalline particles of pure anatase titania were prepared by two different methods. One is the sol-gel method at ambient temperature using ultrasonication (TiO2-SG-US) and conventional stirring method (TiO2-SG-S) and the other by surfactant assisted hydrothermal synthesis (TiO2-HT). More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline titania by sol gel ultrasonication method and hydrothermal synthesis method. The behavior of anatase titania in photocatalytic decomposition of methylene blue in aqueous medium was studied as a function of the method of preparation and the crystallite size. The nanoparticles prepared by ultrasonication method were more effective than both, the sample prepared by conventional stirring method and commercial Degussa P-25. The higher photocatalytic activity of TiO2-SG-US is attributed to the more uniform size of the particles as compared to TiO2-SG-S samples. Both TEM and XRD data on TiO2-HT samples reveal a uniform and nanocrystalline TiO2 particles, which showed photocatalytic activity in both UV and visible region although brookite phase was also present. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Catalytic properties; Nanostructures; Sol-gel chemistry